Acute effect of Ischemic Preconditioning in different blood flow restriction compressions on the an-aerobic performance of trained individuals - Pedro Augusto Mariz Dantas; Jefferson Da Silva Novaes; Carlos Renato Paz; Natalia Herculano Paz; Adenilson Targino Araújo Júnior; Pedro Henrique Marques Lucena; Ana Tereza de Sousa Brito; Thiago Siqueira Paiva Souza; Simoni Teixeira Bittar; Maria do Socorro Cirilo-Sousa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose: to analyze the acute effect of ischemic preconditioning in different compressions of blood flow restriction on the anaerobic performance of trained individuals. Material & methods: the research has a quasi-experimental characteristic, crossed and randomized design, in which the subjects were their own controls and submitted to four experimental conditions before the RAST anaerobic power test: C1 = without IPC; C2 = IPC at 20 mmHg (SHAM); C3 = IPC at 220 mmHg and C4 = IPC at 100% of the auscultatory pulse (AP). The study included 21 trained individuals (21.0 ± 2.3 years), male, who performed the power test after 4 experimental conditions in a randomized manner. Result: Despite the IPC with 100% of the AP demonstrating a positive trend towards the improvement in the averages of Pmax (∆ = 2.6%), Pmed (∆ = 0.7%), Pmin (∆ = 1.8%) and running time in 35 m (∆ = 0.8%), none of the variables showed a significant effect between the experimental conditions. Conclusions: It is concluded that, even presenting a subtle improvement in the maximum, average and minimum powers in a 35-meter running test when using the compression of 100% of the AP, the IPC did not demonstrate a significant increase in performance. However, an increase of 2.6% in maximum power can represent the difference between first and second place in a high-performance test.